Keratoprostheses: from the past to the future - M. V. Grishchenko; V. V. Myasnikova; D. A. Nefedov (Российский офтальмологический журнал, 2023)
The review outlines the models of keratoprostheses currently used in various countries and their effectiveness, conceptual models under development, prospects and trends in keratoprosthetics observed in the world.